2005
DOI: 10.1103/physrevlett.95.076805
|View full text |Cite
|
Sign up to set email alerts
|

Spin Relaxation and Decoherence of Holes in Quantum Dots

Abstract: We investigate heavy-hole spin relaxation and decoherence in quantum dots in perpendicular magnetic fields. We show that at low temperatures the spin decoherence time is two times longer than the spin relaxation time. We find that the spin relaxation time for heavy holes can be comparable to or even longer than that for electrons in strongly two-dimensional quantum dots. We discuss the difference in the magnetic-field dependence of the spin relaxation rate due to Rashba or Dresselhaus spin-orbit coupling for s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
336
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 289 publications
(354 citation statements)
references
References 30 publications
15
336
3
Order By: Relevance
“…The early prediction of greatly reduced hyperfine interaction between hole and nuclear spins, and concomitant increased coherence times [14,15], were confirmed experimentally in systems with small HH-LH mixing realized as selfassembled dots (SADs) [16][17][18] or nanowires [19]. In this regime the strong anisotropy of the hole g-factor is expected [12]. To date, however, only partial anisotropy was demonstrated, e.g., in InAs SADs [20] and silicon nanowires [21].…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…The early prediction of greatly reduced hyperfine interaction between hole and nuclear spins, and concomitant increased coherence times [14,15], were confirmed experimentally in systems with small HH-LH mixing realized as selfassembled dots (SADs) [16][17][18] or nanowires [19]. In this regime the strong anisotropy of the hole g-factor is expected [12]. To date, however, only partial anisotropy was demonstrated, e.g., in InAs SADs [20] and silicon nanowires [21].…”
mentioning
confidence: 77%
“…The hole properties are traced to the amount of HH-LH subband mixing [12,13], which is related to the details of quantum confinement, strain, and the spin-orbit interaction. The early prediction of greatly reduced hyperfine interaction between hole and nuclear spins, and concomitant increased coherence times [14,15], were confirmed experimentally in systems with small HH-LH mixing realized as selfassembled dots (SADs) [16][17][18] or nanowires [19].…”
mentioning
confidence: 99%
“…That is why the electron spin relaxation and decoherence sources in QDs have been intensively studied in the last few years; some more limited number of studies have centered on the hole spin. The main conclusions of these studies are that in moderate magnetic fields (1-10 T) and at low temperature, the electron T e 1 and the hole T h 1 spin-relaxation times are governed by the same mechanism, i.e., the spin-orbitmediated single-phonon scattering, [4][5][6][7][8] which leads to relatively slow relaxation times in the range of milliseconds [9][10][11][12][13] with T h 1 five or ten times smaller than T e 1 . 12 However, the electron-and hole-spin coherence times T e,h 2 have been found to be in the microsecond range up to 15 K, [14][15][16][17] and for higher temperatures T e 2 has shown a sharp decrease 16 related to the modulation by phonons of the hyperfine (hf) interaction with the random fluctuating host nuclear spins.…”
Section: Introductionmentioning
confidence: 99%
“…[28] Several works have theoretically addressed the hole spin relaxation in single QDs taking into account different SOI mechanisms and have showed that one or another prevail depending on the QD traits. [20,29,30,31,32] By comparison, the spin relaxation of holes in DQDs is still poorly understood. This is inspite of their promising prospects for the development of quantum information architectures.…”
Section: Introductionmentioning
confidence: 99%
“…[16,17,18,19] Using the spin of holes in qubits requires control over the hole spin relaxation (T 1 ) and decoherence (T 2 ) times, the latter being related to the former at low temperatures. [20] In the presence of external magnetic fields, the main mechanism of spin relaxation for the valence band is usually phonon scattering mediated by spin-orbit interaction (SOI). [21,22] Indeed, the strong SOI of holes is responsible for some of its characteristic properties, e.g.…”
Section: Introductionmentioning
confidence: 99%